Pulpectomies with Iodoform Versus Calcium Hydroxide-Based Paste: A Preliminary Randomised Controlled Clinical Trial - Maysa Lannes Duarte; Marina Siqueira; Daniele Vieira Cassol; Angela Scarparo; Laura Guimarães Primo; Roberta Barcelos (Association of Support to Oral Health Research (APESB), 2023)
Objective: To compare clinical and radiographical pulpectomy outcomes in primary teeth filled with different pastes. Material and Methods: The sample included thirty-eight teeth indicated for pulpectomy due to irreversible pulp inflammation or necrosis from thirty patients (2 to 9 years old). The first appointment comprised chemomechanical preparation (2.5% sodium hypochlorite), smear layer removal (6% citric acid), intracanal dressing and temporary restoration. Seven days later, teeth were randomly assigned to filling with iodoform (IP) or calcium hydroxide with zinc oxide (CHZO) based pastes and temporarily restored. Final restoration (composite resin) occurred at the 3rd appointment. Data from baseline, 6 and 12 months were analysed using descriptive and inferential statistics (p≤0.05). Results: The overall frequency of success was 63.6% (n=21), with no significant difference between groups (IP=62.5% n=10; CHZO=64.7% n=11, p=0.59). Multiradicular teeth, overfilled canals and teeth whose coronal restoration have been lost were significantly associated with failure (p=0.01, p=0.04 and p<0.001, respectively). Conclusion: After 12 months, both pastes showed similar outcomes and can be used as good options for pulpectomies in primary teeth. Moreover, tooth location, extent of the root canal filling, and integrity of final restoration during the follow-up influenced the outcome of pulpectomies.